The impact of diabetes mellitus on peritoneal dialysis: the Turkey Multicenter Clinic Study - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2014)
Purpose: It is well established that diabetic peritoneal dialysis (PD) patients have a higher mortality rate than the other PD population. This study was designed to determine the overall predictors of survival and compared mortality and morbidity between diabetic and non-diabetic Turkish PD patients. Methods: We conducted a multicenter retrospective study with 915 PD patients [217 had diabetes mellitus (DM)]. Serum albumin, PTH, HbA1c, co-morbid diseases, dialysis adequacy (Kt/V), and peritoneal transport characteristics as well as peritonitis episodes and ultrafiltration failure during the follow-up period were recorded. Results: DM patients were older and had more co-morbidities than non-DM patients. Peritonitis rates were higher in DM patients (one episode per 35.9 patient months) compared to non-DM patients (one episode per 41.5 patient months) (p<0.001). On Kaplan-Meier analysis, patient survival was significantly lower in DM patients with the 2-, 3- and 5-year patient survival rates of 90.8%, 87.8% and 78.2% in non-diabetics and 80.9%, 70.4% and 61.2% in diabetics, respectively. On Cox regression analysis, DM (HR 1.5, p = 0.022), age (HR 1.03, p<0.001), baseline serum albumin (HR 0.39, p<0.001), heart failure (HR 0.038, p = 0.038), peripheral artery disease (HR 1.83, p = 0.025) and amputation (HR 4.1, p = 0.009) at baseline were significant predictors of overall mortality. Conclusions: Patient survival is lower in diabetic compared to non-diabetic patients on PD. Peritonitis rates were also higher in diabetic PD patients. DM, older age, albumin level and cardiovascular co-morbidities are predictors of mortality
Keywords: Diabetes mellitus; mortality; peritoneal dialysis; peritonitis rate; BLOOD-PRESSURE INDEX; CARDIOVASCULAR MORTALITY; GLYCATED HEMOGLOBIN; RISK-FACTORS; CAPD; SURVIVAL; DISEASE; EXPERIENCE